KONJUNGSI RELATIF BAHASA JERMAN DAN BAHASA INDONESIA (Sebuah Studi Kontrastif) - , Abdul Hadi ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This contrastive grammatical research is intended to examine four main problems related to relative clause structure in German and Indonesian. Those problems are: 1) Types of relative conjunctions in German and Indonesian relative clause, 2) The distribution of relative conjunctions in German and Indonesian, 3) The similarities and differences between German and Indonesian relative clause structure and 4) The implication of this research in teaching German and Indonesian as foreign language. This research is a descriptive-qualitative research using contrastive method. In collecting the data, the researcher uses the secondary data from German and Indonesian grammar books applying the formal grammar form of those two languages. The data is taken using observations method and recording technique. Furthermore, the data is analyzed using ultimate constituent analysis. The smallest constituents which considered as the part of this analysis technique are words and phrases in a main clause and subordinate clause as the antecedent and noun in a subordinate clause related to the grammarâs relationship owned by them. The result of this analysis shows that: 1) Types of relative conjunctions in German are declination